2018
DOI: 10.1038/s41598-018-23044-8
|View full text |Cite
|
Sign up to set email alerts
|

3.4 million real-world learning management system logins reveal the majority of students experience social jet lag correlated with decreased performance

Abstract: Misalignments between endogenous circadian rhythms and the built environment (i.e., social jet lag, SJL) result in learning and attention deficits. Currently, there is no way to assess the impact of SJL on learning outcomes of large populations as a response to schedule choices, let alone to assess which individuals are most negatively impacted by these choices. We analyzed two years of learning management system login events for 14,894 Northeastern Illinois University (NEIU) students to investigate the capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 45 publications
3
46
0
3
Order By: Relevance
“…Although light at night from modern electronic devices may be responsible for the circadian disruption affecting the psychiatric diseases discussed above, these devices might also provide the data to help resolve some disease states and improve outcomes. A recent study analyzing digital logon data from nearly 15,000 students reported that circadian disruption (social jet lag) negatively affects learning outcomes, and furthermore that these data could be used to time educational activities to minimize impairments in performance caused by circadian disruption at the individual and population levels 174 . With the prevalence of hand-held and wrist-worn mobile devices today, it may also be possible to leverage data from these devices to predict and monitor psychiatric state of users.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although light at night from modern electronic devices may be responsible for the circadian disruption affecting the psychiatric diseases discussed above, these devices might also provide the data to help resolve some disease states and improve outcomes. A recent study analyzing digital logon data from nearly 15,000 students reported that circadian disruption (social jet lag) negatively affects learning outcomes, and furthermore that these data could be used to time educational activities to minimize impairments in performance caused by circadian disruption at the individual and population levels 174 . With the prevalence of hand-held and wrist-worn mobile devices today, it may also be possible to leverage data from these devices to predict and monitor psychiatric state of users.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, with our increasingly chaotic lifestyles this orderly physiological regulation is steadily being disrupted, which can result in chronodisruption 4,10 . This desynchronization between cellular oscillators in the SCN and peripheral tissues can manifest as negative health outcomes in the form of cardiovascular, metabolic, cognitive and immune dysfunction 4,[10][11][12][13][14] .…”
Section: [H1] Circadian Clocksmentioning
confidence: 99%
“…Sa druge strane radnici u smenama osim čestih zapaljenskih reakcija imaju hormonski disbalans (sa povećanom koncentracijom rezistina, grelina, leptina i adiponektina, lipokalina-2, melatonina i kortizola), kao i česte mutacije gena indukovane oksidativnim stresom. Usled desinhronizacije ritmičkih sistema kod radnika u smenama se događa spavanje na poslu, smanjena efikasnost, poremećen raspored za odmor, izmenjen porodični i socijalni život i povećan je rizik od razvoja malignih bolesti (14,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Hronopatologija: Bolesti Sa Poremećenim Ciklusomunclassified